2010
DOI: 10.1097/pec.0b013e3181d6d9c8
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Child Care Centers in Pennsylvania With National Health and Safety Performance Standards for Emergency and Disaster Preparedness

Abstract: Although many of the child care centers we surveyed are in compliance with the recommendations for emergency and disaster preparedness, specific areas for improvement include increasing the frequency of practice of the WEP, establishing specific written procedures for external disasters and urgent medical emergencies, maintaining the immediate availability of potentially life-saving medications, and ensuring that all child care center staff are trained in first aid and CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…This is also in keeping with other studies from North America, which found that 30% of teachers had no specific training in first aid, and 40% had never been trained in CPR [26,27]. One U.S. study found that only 75% of child care center administrators surveyed reported that first aid training was required for their staff, and only 15% of child care centers serving children with special care needs required its staff to be CPR-certified [3]. In the U.S., approximately half of all child care centers do not have specific written procedures for urgent medical emergencies, such as severe bleeding, unresponsiveness, poisoning, shock, heart or circulation failure, seizures, head injuries, anaphylaxis, or allergic reactions [3].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is also in keeping with other studies from North America, which found that 30% of teachers had no specific training in first aid, and 40% had never been trained in CPR [26,27]. One U.S. study found that only 75% of child care center administrators surveyed reported that first aid training was required for their staff, and only 15% of child care centers serving children with special care needs required its staff to be CPR-certified [3]. In the U.S., approximately half of all child care centers do not have specific written procedures for urgent medical emergencies, such as severe bleeding, unresponsiveness, poisoning, shock, heart or circulation failure, seizures, head injuries, anaphylaxis, or allergic reactions [3].…”
Section: Discussionsupporting
confidence: 84%
“…One U.S. study found that only 75% of child care center administrators surveyed reported that first aid training was required for their staff, and only 15% of child care centers serving children with special care needs required its staff to be CPR-certified [3]. In the U.S., approximately half of all child care centers do not have specific written procedures for urgent medical emergencies, such as severe bleeding, unresponsiveness, poisoning, shock, heart or circulation failure, seizures, head injuries, anaphylaxis, or allergic reactions [3]. The American Academy of Pediatrics recommends that at least one staff member who has successfully completed training in pediatric first aid be in attendance at all times and in all places where children are present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] The objective of our study is to determine the compliance of middle school-aged babysitters in central Pennsylvania with national recommendations for emergency preparedness and safety practices, to identify types of emergency situations encountered by babysitters, and to determine areas in which additional education regarding emergency preparedness and safety are required.…”
Section: Introductionmentioning
confidence: 99%
“…Children and adults may experience medical emergency situations because of injuries, complications of chronic health conditions or unexpected major illnesses that occur in school. 2 Emergencies require urgent intervention, in order to save life or property or avoid worsening of damage. The sources of emergencies may be medical e.g.…”
Section: Introductionmentioning
confidence: 99%